A DNA Methylation Signature of Addiction in T Cells and Its Reversal With DHEA Intervention - Lax, Elad; Warhaftig, Gal; Ohana, David; Maayan, Rachel; Delayahu, Yael; Roska, Paola; Ponizovsky, Alexander M.; Weizman, Abraham; Yadid, Gal; Szyf, Moshe (Frontiers in Molecular Neuroscience, 2018)
Previous studies in animal models of cocaine craving have delineated broad changes in DNA methylation profiles in the nucleus accumbens. A crucial factor for progress in behavioral and mental health epigenetics is the discovery of epigenetic markers in peripheral tissues. Several studies in primates and humans have associated differences in behavioral phenotypes with changes in DNA methylation in T cells and brain. Herein, we present a pilot study (n=27) showing that the T cell DNA methylation profile differentiates persons with a substance use disorder from controls. Intervention with dehydroepiandrosterone (DHEA), previously shown to have a long-term therapeutic effect on human addicts herein resulted in reversal of DNA methylation changes in behavioral pathways associated with the addictive state.